Aspergillus species associated with grains of groundnuts (Arachis hypogaea L.) and common beans (Phaseolus vulgaris L.) cultivated in Costa Rica - Carranza-Mesén, Fabiola; Blanco-Meneses, Mónica; Granados-Montero, Maria del Milagro; Vinas Meneses, Maria (Agronomía Mesoamericana, 2022)
Introduction. Common beans (Phaseolus vulgaris L.) and peanuts (Arachis hypogaea L.) are legumes, widely consumed in developing countries. However, those grains could be contaminated with Aspergillus, a genus of fungus that includes mycotoxin-producing species. Objective. To identify the Aspergillus species that colonize the grains of common beans and peanuts in Costa Rica and to identify atoxigenic strains of A. flavus. Materials and methods. Eighty-three samples of common bean grains and nineteen samples of peanuts were collected during the years 2019 and 2020 in regions where those grains are produced in Costa Rica. All samples were used to isolate and identify Aspergillus species by partial sequences of ITS (internal transcribed spacer) and cmd (calmodulin) genes. Atoxigenic strains of A. flavus were also identified by chemical and molecular methods. Results. 46 % and 32 % of the collected common beans and peanuts samples, respectively, were contaminated with Aspergillus spp. In common beans, 85 isolates of Aspergillus were obtained, most of them belonging to A. flavus and A. niger species. Most of the A. flavus isolates were obtained from the Cabécar (fifteen isolates) and Nambí (seven isolates) common bean varieties, while A. niger was mostly isolated from the Cabécar variety (eleven isolates). In the case of peanuts, thirteen isolates were obtained, most of them identified as A. niger. No atoxigenic strains were found in peanuts, however, in common beans, five strains of A. flavus with this characteristic were found. Conclusions. The present study demonstrated the diversity of Aspergillus species that colonize the grains of common beans and peanuts in Costa Rica. Most of the species isolated are producers of mycotoxins that cause adverse effects on human health.